Advance Directives: Declaraciones Anticipadas de tratamiento médico o mal denominado Testamento Biológico - Zappalá, Francesco (2023)
The main issue of Advance Directives is determ ining the effectiveness and validity of the will conferred by the informed consent signed in capacity, which aims to interpret the intent of the patient for a future time in whic h he will be in a state of inab ility to decide on treatments and medical provisions. There are guidelines that differentiate Advance Directives in common law and civil law systems, which must be identif ied in order to understand the law and legal practices that relate to them and to address a comparative study of this institution in Western legal culture. Advance Directives have been conf used with the living will, because of a mistaken duplication of legislation. In the collective imagination the consequences of Advance Directives coincide with euthanasia, especially in the pa ssive rather than in the active mode. However, these are two different concepts, with close conn ections, but with different legal regulation, to such an extent that Continental Europe accepts A dvance Directives, and they are part of society, as opposed to euthanasia, which is excluded le gislatively, although it has wide acceptance in common law systems.